A High‐Efficiency, Portable, Solar‐Powered Cooling System Based on a Foldable‐Flower Mechanism and Wireless Power Transfer Technology for Vehicle Cabins. Issue 6 (6th April 2020) - Zhang, Tingsheng; Feng, Yan; Wu, Xiaoping; Pan, Yajia; Zhang, Zutao; Yuan, Yanping
Abstract : In summer, the high temperature inside vehicles is a problem, because cooling a vehicle parked under the scorching sun is both time and energy consuming. Herein, a portable solar‐powered cooling system (SPCS) is proposed based on a foldable‐flower mechanism and wireless power transfer (WPT) technology. The proposed system consists of three main parts: a solar foldable‐flower module (SFFM), an energy transfer module, and a temperature control module. The SFFM is a novel foldable mechanism that achieves a high space utilization through a rotating process and a folding process, like a flower opening its petals. The SFFM, equipped with photovoltaic (PV) cells, collects solar energy and converts it into electricity. The energy transfer module stores electricity from the SFFM in a supercapacitor via a WPT unit. The temperature control module achieves automatic temperature regulation using a cooling device. Experimental results show that output power reaches up to 7.571 W with a load resistor of 5 Ω, whereas the efficiency of the WPT reaches up to 73.6% with a load resistor of 15 Ω. Moreover, thermal simulation results illustrate that the proposed system achieves an average temperature reduction of 27.45 °C, making it feasible and effective to cool a hot vehicle cabin. Abstract : A portable solar‐powered cooling system (SPCS) is proposed to cool cabins of vehicles parked under the scorching sun. A novel foldable‐flower mechanism is designed to collet solar energy. Meanwhile, wireless power transfer technology is applied to cooling systems of vehicles. Experiment and simulation results indicate that the SPCS has a considerable effect on cooling the vehicle cabin.